PEMIKIRAN EKONOMI ISLAM DI KERAJAAN-KERAJAAN ISLAM DI INDONESIA (STUDI SEJARAH DAN IMPLEMENTASI) - Titin Hardianti; Mukhtar Lutfi; Nasrullah Bin Sapa (CV. Adiba Aisha Amira, 2025)
This research raises Islamic economic thought in Indonesia by looking at its history and implementation. The existence of Islamic kingdoms such as Samudera Pasai, Demak, Aceh Darussalam, Banten, and Ternate strengthens the position of Islam as a system that regulates various aspects of life. These kingdoms played a strategic role in integrating Islamic values into their economic policies. This study is a literature review study, where this study tries to explore and analyze facts from various scientific sources that are accurate and valid. The results of this study state that the implementation of Islamic economic thought in Islamic kingdoms in Indonesia not only contributes to economic progress, but also strengthens social values such as solidarity, justice, and blessings in the lives of the people. This economic system based on sharia principles provides an important example of how the integration between religion.